Competence of the Sri Lankan Apparel Exports in the International Apparel Market - Umashankar, K. (Sri Lanka Agricultural Economics Association, 2011)
The primary aim of this research is to quantify and analyze the impact of the elimination of quota system on the US import demand for two of the leading Sri Lankan export apparel categories of knitted crocheted and not knitted and crocheted, respectively in the US market. Monthly import data from 1998 to 2009 were analyzed using the linear version of the almost ideal demand system (LA/AIDS. Results suggest that quota elimination opens up the opportunity to Sri Lanka and the markets will no longer be restricted. The income elasticity of 1.9 at 1% significance level reflects relative competitive position of Sri Lanka in the US import market. The computed income elasticities for other countries provide evidence on the level of competition from Bangladesh, Indonesia, India and more specifically from China. Generally, small, positive and significant value of the cross-price elasticity of Sri Lankan apparels manifested a weak substitute between Bangladesh (0.03), China (0.02), India (-0.01), Vietnam and the US. This stands as an evidence for the competence of the Sri Lankan apparel sector in the US market. Therefore, this research propose further diversification, integration and productivity improvements to the Sri Lankan apparel sector as the key issues to successfully face intense competition in the US market
Keywords: Sri Lanka; United States; Apparel industry; Quota; LAIDS